2017
DOI: 10.1016/j.dld.2017.03.001
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in liver stiffness values obtained with new ultrasound elastography machines and Fibroscan: A comparative study

Abstract: The present results showed only moderate concordance of the majority of elastography machines with the Fibroscan results, preventing the possibility of the immediate universal adoption of Fibroscan thresholds for defining liver fibrosis staging for all new machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 18 publications
(20 reference statements)
2
39
0
1
Order By: Relevance
“…A daily LSM assessment, which is hardly practicable in the actual clinical setting, could identify the real advantages of TE for assessing LSM. Another limitation is that in this study, we assessed LSM only by TE, and thus it is difficult to compare our findings with results obtained with other ultrasound-based elastography techniques, as demonstrated recently [44]. Nevertheless, even though a dedicated device is needed, TE is still considered the best validated and readily available elastography technique, and most centers use TE as a standard technique to assess LSM even in the consolidated hepatologic indications [38,45,46].…”
Section: Discussionmentioning
confidence: 88%
“…A daily LSM assessment, which is hardly practicable in the actual clinical setting, could identify the real advantages of TE for assessing LSM. Another limitation is that in this study, we assessed LSM only by TE, and thus it is difficult to compare our findings with results obtained with other ultrasound-based elastography techniques, as demonstrated recently [44]. Nevertheless, even though a dedicated device is needed, TE is still considered the best validated and readily available elastography technique, and most centers use TE as a standard technique to assess LSM even in the consolidated hepatologic indications [38,45,46].…”
Section: Discussionmentioning
confidence: 88%
“…Results of TE, RTE and ARFI previously demonstrated that malignant FLL were generally stiffer than benign lesions; however, this evidence was obtained in relatively small studies and the used techniques are not fully capable to provide an extensive qualitative and quantitative elasticity analysis in FLL. It should be appreciated at this point that different elastographic methods should not be considered identical and that cut‐off values of liver stiffness are not interchangeable between them . Therefore, the results of one method (for example, mean stiffness and cut‐off value between benign and malignant FLL as obtained by RT‐2D‐SWE) could not be extrapolated and used as such for the other elastographic method (for example pSWE).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods of calculating liver stiffness have the potential to yield variable results, and even among manufacturers using the same techniques, different measured values may be obtained . The work flow and data acquisition are also unalike between machines and may affect reliability, especially for an inexperienced operator.…”
mentioning
confidence: 99%